Obesity in adolescents with intellectual disability: Prevalence and associated characteristics. Issue 5 (September 2016) - Krause, Sharon; Ware, Robert; McPherson, Lyn; Lennox, Nicholas; O'Callaghan, Michael
Summary: Objective: Studies from a number of countries have indicated an increased risk of obesity in adolescents with intellectual disability. Whether risk factors for adults with intellectual disability apply to adolescents however is uncertain. This study examines obesity in a community sample of adolescents with intellectual disability in Australia, and investigates risk factors associated with obesity and overweight. Methods: A cross-sectional survey and medical record review on 261 adolescents with intellectual disability attending special education facilities in South-East Queensland, Australia between January 2006 and September 2010 was conducted. Information on age, gender, weight, height, syndrome specific diagnoses, problematic behaviours, mobility, taking psychotropic or epileptic medication, and perceived household financial difficulties was collected. Body mass index (BMI) was calculated and participants categorised as normal/underweight, overweight or obese according to the International Obesity Taskforce definitions. Results: Overall 22.5% (95% CI: 17.8–28.0%) of adolescents were obese, and 23.8% (95% CI: 19.0–29.4%) were overweight, a marked increase compared to Australian norms. Adolescents with Down syndrome were more likely to be obese than other participants (odds ratio = 3.21; 95% CI: 1.41–7.30). No association was found with other risk factors examined. Conclusions: Prevalence of obesity and overweight were increased compared to general Australian adolescents. The only significant risk factor was the presence of Down syndrome. These findings reinforce the need for a health policy and practice response to obesity that is inclusive of individuals with intellectual disability.